EVALUATION STUDY OF FLOOD DISASTERS IN KELAPA GADING - Wardaningrum, Anastasia Septya; Sudinda, Teddy (Jurnal Teknik Sipil, 2022)
Kelapa Gading is one of the sub-districts in North Jakarta that is often hit by floods, so it is necessary to analyze the causes of flooding and how to overcome them. According to the calculations performed using the Manning Formula, whose results then compared with the planned discharge calculated using the Rational Method, it is established that there are 18 channels from 33 drainage channels which are unable to accommodate runoff discharge that may occur within a 5-year period. Thus, for a period of 10 years, there are 20 channels that are unable to accommodate the existing runoff discharge. Furthermore, from 10 Pumping Stations in a ten years rainy period, there are four pumps that are unable to accommodate runoff discharge with the assumption of 0.2 m inundation. Meanwhile, assuming a 0.5 m inundation, there are seven pumps that cannot accommodate the existing runoff discharge. Therefore, suggestions that can be given to reduce flooding in Kelapa Gading are to enlarge the existing drainage channel and add pumps according to the recommendations. Lack of land infiltration also causes flooding therefore, it is necessary to build 617infiltration wells which are constructed at various points in Kelapa Gading thus making flooding does not occur again.